Penguatan Tata Kelola Pascasarjana melalui Digitalisasi Layanan Akademik - Mahirun Mahirun; Ade Dedi Rohayana; Mutiara Syaffa Ahliansyah; Titi Rahayu Prasetiani; Danang Satrio; Amalia Ilmiani (Jurnal Pengabdian Masyarakat Akademisi, 2026)
The community service activity was conducted in the form of a workshop on postgraduate governance with the theme “Digitalization of Academic and Administrative Governance toward an Excellent Postgraduate Institution in the Development of Science and Religion”. It was aimed at postgraduate program managers, lecturers, administrative staff, and information system operators, with the objective of enhancing their capacity to implement effective governance and optimize the digitalization of academic services to achieve a more efficient, transparent, and competitive system. The workshop was carried out through the delivery of materials on governance and digitalization of academic and administrative services, followed by practical sessions on the implementation of digital systems. The results of the activity indicate an improvement in participants understanding and skills in managing postgraduate governance and implementing digital academic service systems, as evidenced by the formulation of follow up action plans and a shared commitment to applying more efficient, transparent, and accountable management practices. Based on the evaluation of this community service activity, a follow up initiative was identified, namely the development of a digital system for managing students final projects, including theses and dissertations.